The Cry of the Child and its Relationship to Hearing Loss in Parental Guardians and Health Care Providers. Issue 2 (3rd March 2016) - Calderon, Lindsay E.; Carney, Logan D.; Kavanagh, Kevin T.
Abstract : In this study the authors investigate the sound pressure levels produced by crying children and discuss the possible adverse effects that direct exposure may impose on a tending guardian or healthcare professional. Sound intensity levels from various pediatric patients ( N  = 26) were measured under two segregate conditions, one imitating the exposure of an examining physician and the other resembling that of parental guardians. Interestingly, all of the recorded sound levels fell between 99–120 dB(A) of sound pressure; children presenting the greatest risk for intense cries with potentially harmful sound intensities were between the ages of 9 months and 6 years. The authors found that elevated noise levels produced from crying children can cause acute discomfort and mild pain to those exposed. In addition, there is a theoretical risk that chronic exposure to these intense sound pressures may result in noise-induced hearing loss in a parental guardian or an examining physician. Parents of young children may be more likely to succumb to impulsive reactions in attempting to arrest the crying, which could be a precipitating factor for child abuse, responding to physical stress as much as emotional stress. Social workers and medical personnel should consider suggesting the use of ear plugs by parental guardians of frequently crying children as a modality for the prevention of child abuse.